Konsentrasi Nutrien di Saluran Pembuangan Kota Makassar: Sebuah Survei Awal - Hanafi, Sulfikar; Purnama, Jumri (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2012)
DOWNLOAD PDFThe drainage system in Makassar City of Indonesia is intended to efficiently deliver waste water (stormwater and greywater) to the receiving waters downstream. There is no wastewater processing plant available. Thus, waste water, from households and industries located in residential areas was delivered directly to the drainage system. Nutrients, like nitrogen and phosphorus, contained in the waste water was also delivered to the receiving waters. There is no data available on how much nutrient has entered the receiving waterbodies. We conducted a survei on the concentration of total- and soluble- nitrogen and phosphorus in surface water of Sinrijala Drainage and Pampang River that drained a heavily populated area in this city in November 2009. The cadmium reduction method was used to measure nitrogen, and the ascorbic acid method for phosphorus. Our survey showed that the surface water was potentially very eutrophic at the time of sampling. The concentration of TN (0,056-3,697 mg/L), TP (3,140-13,03 mg/L), and the respective soluble species (FRP: 0,028-2,935 -NO3-N: 0,187-0,601 mg/L) were well beyond the internationally accepted levels. The probable sources of these nutrients were domestic waste like deterjent, food scrapes and human waste. Key words: Nutrients concentration, total nitrate, total phosphorus, nitrate-nitrogen, nitrite-nitrogen, urban drainage, Makassar.